Multiple Cases of Cutaneous Mycobacterium massiliense Infection in a “Hot Spa” in Japan - Nakanaga, Kazue; Hoshino, Yoshihiko; Era, Yuko; Matsumoto, Kentaro; Kanazawa, Yuji; Tomita, Atsuko; Furuta, Masanari; Washizu, Motohisa; Makino, Masahiko; Ishii, Norihisa (Journal of Clinical Microbiology, 2011)
Article Usage Stats Services JCM Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue JCM About JCM Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy JCM RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0095-1137 Online ISSN: 1098-660X Copyright © 2014 by the American Society for Microbiology. For an alternate route to JCM .asm.org, visit: JCM